Full report on roundtable on place management and placemaking in Singapore - HOE, Su Fern (Institutional Knowledge at Singapore Management University, 2016)
In Singapore, the government has adopted a strategy it calls “place management” to inject“heart and soul” into the city. These efforts include the greening of streets, providing benches,closing roads for pedestrian access, and public activities and arts-centred events such as thei Light Marina Bay festival and the Singapore Night Festival. Cities like New York and Parishave also attempted a similar strategy known as “placemaking” to develop human-centredplaces and improve the quality of life for their residents. “Creative placemaking”, a relatedconcept, has also emerged to refer to the use of arts and culture to animate public spacesand neighbourhoods. However, despite their growing popularity, place management andplacemaking remain vague concepts.